Digital outpatient health solutions as a vehicle to improve healthcare sustainability—a United Kingdom focused policy and practice perspective - Brown, Matthew R. D.; Knight, Matthew; Peters, Christopher J.; Maleki, Simin; Motavalli, Ali; Nedjat-Shokouhi, Bahman (Frontiers in Digital Health, 2023)
In the midst of a global climate emergency and with health care systems across the world facing extreme pressure, interest in digital approaches as a potential part-solution to these challenges has increased rapidly. The evidence base to support the role that digitalization can play in moving towards more sustainable models of healthcare is growing, as is the awareness of this key area of healthcare reform amongst policy makers, clinicians and the public. In this policy and practice review we explore four pillars of healthcare sustainability - environmental, economic, patient and clinician, delineating the potential impact that digitally enabled healthcare can have on each area. Additionally, real-world examples are provided to illustrate the impact individual digital interventions can have on each pillar of sustainability and delineate the scale of the potential benefits which can be achieved.